The relationship between abusive supervision, distributive justice and job satisfaction: A substitutes for leadership approach - Velez, M. J.; Neves, P. (Revue Européenne de Psychologie Appliquée / European Review of Applied Psychology, 2017)
Introduction Recently, interest in abusive supervision has grown (Tepper, 2007). However, little is still known about organizational factors that can reduce the adverse effects of abusive supervision. Objective Based on a substitute for leadership perspective (Kerr & Jermier, 1978), we predict that job resources adequacy and role clarity act as buffers in the negative relationship between abusive supervision, distributive justice and job satisfaction. Method A sample of 253 employees from a City Hall was used to test our hypotheses. Results We found that abusive supervision was significant and negatively related to distributive justice when job resources adequacy and role clarity were low, but not when job resources adequacy and role clarity were high, with consequences for job satisfaction. Conclusions These findings suggest that job resources adequacy and role clarity can reduce the negative impact of abusive supervision, which then lessens distributive unfairness perceptions and job dissatisfaction.